Energetical characteristics of nitrogen-dopedcobalt oxide for hydrogen production - Каптагай , Г. А.; Айдарбекова , А.; Достан , Г. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article presents the results of a theoretical study of water adsorption on a nitrogen-doped Co 3 O 4 (100) plate within the framework of the density functional theory (DFT) combined with the Hubbard-U approximation and statistical thermodynamics. Experimental results show that the catalytic activity of Co 3 O 4 for the oxygen evolution reaction (OER) can be improved by doping with nitrogen. The article discussesthe effects of changes in the catalytic properties of the plate arising due to nitrogen admixture. The authors have calculated excess potentials based on the Gibbs free energy scheme on a nitrogen-doped surface. The authors present a preliminary simulation of OER on an N-doped Co 3 O 4 surface with different concentrations of dopant and its spatial distribution around the Co oct and Co tet adsorption sites. The overvoltage was calculated for two adsorption sites on seven types of N-doped Co 3 O 4 surfaces. The highest calculated overvoltage value for a surface doped with N is ∼ 1 V.